Timing is everything: how planting period shapes nutritional quality, mycobiota characteristics, and mycotoxin contamination in maize (Zea mays) grains - Pérez-Pizá, M.C.; Vicente, S.; Castellari, Claudia Carla; Mousegne, Fernando Jorge; Jecke, Fernando Ariel; Cornejo, Paula; Ibañez, Verónica Noé; Sansinena, M.J.; Vago, M.E.; Stenglein, Sebastian Alberto; Pacin, Ana Maria (Springer Nature, 2024)
Maize (Zea mays L.) is crucial in global grain markets and food/feed production. Fungal contamination in ears can adversely affect crop yield and diminish the nutritional value of grains. Moreover, many of the main pathogens affecting maize are producers of mycotoxins, which pose a risk to food safety. The area under late-planted maize in Argentina has increased, as more stable yields despite lower potential are expected in comparison to the early planting period. However, late-planted maize is prone to fungal infections and insect damage as well as mycotoxin contamination. This study aimed to evaluate the influence of maize planting periods (early vs. late) on grain nutritional quality, grain mycobiota, mycotoxin levels, and their interrelationships. Two experiments were conducted at Buenos Aires (Argentina) using thirteen genetically stable maize hybrids. Early planting occurred on October 5 (2020) whereas late planting was performed on December 12 (2020). Grain yield, number of grains per square meter, and thousand grain weight were measured at harvest and representative samples of grains were used for the laboratory analyses. The results demonstrated that early-planted maize exhibited high grain nutritional quality and low levels of toxigenic fungal mycobiota. In contrast, late-planted maize displayed low nutritional quality, increased presence of toxigenic mycobiota, and high contamination with elevated levels of fumonisins (a major mycotoxin). This study highlights the impact of planting period on grain yield, grain quality, and mycotoxin contamination, and it emphasizes the need for more research and regulatory considerations in this field.